ANALISIS PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN DAN KEPUASAN KERJA SEBAGAI INTERVENING VARIABEL PADA CV. SOLUSI OFFSET YOGYAKARTA (Studi Kasus Pada Karyawan CV. Solusi Offset Yogyakarta) - Handoyo Handoyo (JURNAL EKOBIS DEWANTARA, 2018)
Abstract The Study was aimed to describe the influence (1) the influence of quality of work life on the performance of employees CV. Offset Solutions Yogyakarta, (2) the influence of quality of work life on to job satisfaction CV. Offset Solutions Yogyakarta, (3) the influence of quality of work life to organizational commitment CV. Offset Solutions Yogyakarta, (4) the influence of organizational commitment to the performance of employees CV. Offset Solutions Yogyakarta, (5) the effect of job satisfaction on employee performance CV. Offset Solution Yogyakarta. The type of research is exsplanatory research. Its population were 50 employees CV. Offset Solution Yogyakarta. Number of samples were 50 respondents by using saturated sampling technique (census). Methods of data collection were conducted with questionnaire media, while data analysis techniques used simple linear regression analysis and multiple linear regression analysis. The result of the research shows that (1) the quality of working life does not affect the organizational commitment, (2) the quality of work life affect the job satisfaction, (3) the quality of working life has no effect on employee performance, (4) organizational commitment has no effect on employee performance, (5) job satisfaction affect on employee performance. The results of the study were determined by significance level α = 5%.